PENGARUH ENTREPRENEURIAL PASSION TERHADAP KEINGINAN BERWIRAUSAHA DI INDONESIA - Rizqi Anantia; Edy Yulianto Putra; Dessy Aliandrina (Jurnal Ilmiah Satyagraha, 2022)
Theory of planned behavior (TPB) consisting of personal attitude,subjective norms and perceived behaviour control are the model study about therelation of intention and behaviour. In order to expand TPB, entrepreneurial passionvariabel is inserted, which is emotion effected to entrepreneur behaviour. In thisresearch by adding predictor variabel in TPB, it is expected to enrich theexplanation of entrepreneurial intention.The object of this research is entrepreneur in Indonesia. The sampling techniqueused is purposive sampling methode. This research uses primary data, the result ofdata collection using a questionnaire. The collected data had been processed using SPSS software version 24.0. Hypothesis testing analysis uses linear regression andpath analysis.The result of the research is entrepreneurial passion significantly and positevelyaffected entrepreneurial intention. In TPB, each construc effects entrepreneurialintention differently. Personal attitude and perceived behavioral control effectentrepreneurial intention significantly and positevely, while subjective norm affectsignificantly and negatively. Regarding intervening variable, personal attitude andperceived behavioral control has succesfully became intervenig variable betweenentrepreneurial passion and entrepreneurial intention.